Etrolizumab-s fails to control E-Cadherin-dependent co-stimulation of highly activated cytotoxic T cells - Wiendl, Maximilian; Dedden, Mark; Liu, Lijuan; Schweda, Anna; Paap, Eva-Maria; Ullrich, Karen; Hartmann, Leonie; Wieser, Luisa; Vitali, Francesco; Atreya, Imke; Müller, Tanja; Günther, Claudia; et al. (Nature Communications, 2024)
Despite promising preclinical and earlier clinical data, a recent phase III trial on the anti-β7 integrin antibody etrolizumab in Crohn’s disease (CD) did not reach its primary endpoint. The mechanisms leading to this outcome are not well understood. Here we characterize the β7+ T cell compartment from patients with CD in comparison to cells from individuals without inflammatory bowel disease. By flow cytometric, transcriptomic and functional profiling of circulating T cells, we find that triple-integrin-expressing (α4+β7+β1hi) T cells have the potential to home to the gut despite α4β7 blockade and have a specific cytotoxic signature. A subset of triple-integrin-expressing cells readily acquires αE expression and could be co-stimulated via E-Cadherin-αEβ7 interactions in vitro. Etrolizumab-s fails to block such αEβ7 signalling at high levels of T cell stimulation. Consistently, in CD patients treated with etrolizumab, T cell activation correlates with cytotoxic signatures. Collectively, our findings might add one important piece to the puzzle to explain phase III trial results with etrolizumab, while they also highlight that αEβ7 remains an interesting target for future therapeutic approaches in inflammatory bowel disease.
CRIS-Team Scopus Importer:2024-02-16